Nucleo‐plastidic PAP8/pTAC6 couples chloroplast formation with photomorphogenesis. (1st October 2020) - Liebers, Monique; Gillet, François‐Xavier; Israel, Abir; Pounot, Kevin; Chambon, Louise; Chieb, Maha; Chevalier, Fabien; Ruedas, Rémi; Favier, Adrien; Gans, Pierre; Boeri Erba, Elisabetta; Cobessi, David; et al.
Abstract: The initial greening of angiosperms involves light activation of photoreceptors that trigger photomorphogenesis, followed by the development of chloroplasts. In these semi‐autonomous organelles, construction of the photosynthetic apparatus depends on the coordination of nuclear and plastid gene expression. Here, we show that the expression of PAP8, an essential subunit of the plastid‐encoded RNA polymerase (PEP) in Arabidopsis thaliana, is under the control of a regulatory element recognized by the photomorphogenic factor HY5. PAP8 protein is localized and active in both plastids and the nucleus, and particularly required for the formation of late photobodies. In the pap8 albino mutant, phytochrome‐mediated signalling is altered, degradation of the chloroplast development repressors PIF1/PIF3 is disrupted, HY5 is not stabilized, and the expression of the photomorphogenesis regulator GLK1 is impaired. PAP8 translocates into plastids via its targeting pre‐sequence, interacts with the PEP and eventually reaches the nucleus, where it can interact with another PEP subunit pTAC12/HMR/PAP5. Since PAP8 is required for the phytochrome B‐mediated signalling cascade and the reshaping of the PEP activity, it may coordinate nuclear gene expression with PEP‐driven chloroplastic gene expression during chloroplast biogenesis. Synopsis: PAP8, an essential subunit of the chloroplast‐encoded RNA polymerase in Arabidopsis thaliana, is required for phytochrome‐B‐mediated photomorphogenesis by modulating both nuclear and chloroplast‐encoded gene expression during chloroplast biogenesis. The bZIP transcription factor HY5 promotes PAP8 expression. PAP8 is localized and active in both plastids and the nucleus. PAP8 is essential for the formation of late photobodies. PAP8 is required for various PHYB‐dependent photoresponses, e.g., regulation of PIF1/3 stability and expression of GLK1/2 transcription factors. PAP8 interacts with PAP5/HMR and drives photosynthesis‐associated plastid‐encoded gene (PhAPG) expression. Abstract : The plastidial RNA polymerase subunit PAP8 promotes chloroplast biogenesis in response to light via phytochrome B regulation of both skotomorphogenic and photomorphogenic factors in Arabidopsis thaliana .